Management of Ankyloglossia Using Conventional Surgical Technique: A Case Series - Bhoir VV; Gujar DA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2024)
Periodontal plastic surgery is a more conservative and precise technique practised to create more functional and aesthetic results for the treatment of mucogingival problems. The presence of an aberrant frenum is one of the aetiological factors associated with the persistence of a midline diastema. Inadequate dental plaque removal, poor oral hygiene, bifid tongue, impaired speech, and mucogingival problems like recession and black triangles need more attention. Ankyloglossia, or tongue-tie, is a congenital anomaly with an abnormally short lingual frenulum. The aberrant frenum can be treated with surgical removal of the frenum using either frenectomy or frenotomy procedures. In the present case series, frenectomy was performed using a conventional scalpel technique for the treatment of tongue tie.